Disentangling the Taxonomy of the Mahseers (Tor spp.) of Malaysia: An Integrated Approach Using Morphology, Genetics and Historical Records. Issue 3 (3rd July 2017) - Walton, S. E.; Gan, H. M.; Raghavan, R.; Pinder, A. C.; Ahmad, A.
ABSTRACT: The establishment of appropriate taxonomic designations is essential for the effective management of fishery resources. Despite over a century of explorations and research, the cyprinid genus Tor represents a group of large-bodied freshwater fishes whose taxonomy and systematics remains poorly known. While five species of Tor are currently listed as "endangered" on the IUCN Red List, a further five out of 18 species currently recognized are assessed as "data deficient, " with at least one undescribed species, believed to be on the brink of extinction (i.e., the Humpback Mahseer endemic to the Cauvery River in India). Tor mahseers represent a suitable model for the application of an integrated approach using morphology, genetics, and historical records to resolve species identities, where one or more of these fundamental approaches may have been deficient in the past. Focusing specifically on the taxonomy and nomenclature of the Tor species recorded from Peninsular Malaysia, one of the aims of this review is to define the identity of two nominal species, T. tambra and T. tambroides . Original descriptions of these two nominal species contain little or practically no characters to distinguish them, and partly explains why secondary literature fails to conclusively determine species boundaries. A phylogenetic analysis of mahseer specimens from this region, based on publicly available and newly sequenced mitochondrial COX1 genes, does not support species designation based on previously established morphological features. More importantly, multiple tree-based species delimitation approaches showed that previously sequenced T. tambroides from Peninsular Malaysia and the newly described Tor species from Vietnam could not be delimited from the topotypic Tor tambra . A wider investigation of mahseer taxonomy covering all of Southeast Asia, using such an integrated approach is recommended to resolve the ambiguous taxonomy and is of profound importance for the conservation and management of exploited and farmed populations of these highly valued and iconic fish.